Quality assessment of Physical Education in Shahriar city based on SERVQUAL model - Monazami, A.; Karami, F.; Shahbazi, M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The objective was to assess the quality of Physical Education in secondary schools of Shahriar city using the SERVQUAL model. The sample consisted of 336 (217 males and 119 females) secondary school students of Shahriar in 2019-2020. The distribution of the students was: 166 students (49.4%) of tenth grade, 132 students (39.5%) of eleventh grade and 38 students (11.1%) of twelfth grade. An adaptation of SERVQUAL questionnaire was the instrument used, with the title “Quality of Service in Physical Education” (Cronbach’s alpha=0.949). Data were analyzed with SPSS 16. The quality of the desirable educational services was significantly (p<0.01) higher than the quality of the available educational services in all the dimensions studied: Tangibles, Reliability, Responsiveness, Assurance, Empathy. For tenth grade students, the most important dimension was tangibles and the least important was responsiveness. For eleventh grade students, the most important dimension was assurance and the least important was responsiveness. For twelfth grade students, the most important dimension was assurance and the least important was empathy. The findings of this study can be used to improve education quality in schools, particularly in Physical Education.